Validasi Metode Bioanalisis Vankomisin HCl dalam Spiked-plasma Manusia Menggunakan KCKT-UV untuk Aplikasi PKOD - Ari Wibowo; Damas Inggil Maulidina; Wahyuni Shalatan Fitri; Vitarani Ningrum (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
As the first-line antibiotic for the treatment of infections caused by methicillin-resistant Staphylococcus aureus (MRSA), vancomycin has a narrow therapeutic index with high pharmacokinetic variability. Therefore, it is deemed necessary to examine its concentration in the blood as a strategy to monitor the fulfillment of therapeutic levels in patients receiving vancomycin. This study aimed to validate vancomycin bioanalysis in spiked-human plasma for the applications of therapeutic drug monitoring (TDM).